Grace Above All - St. Anthony, Jane (Book collections on Project MUSE., 2015)
When thirteen-year-old Grace, her mother, and four siblings go to her mother's childhood cabin by a lake over the summer, as usual Grace is in charge of all the kids while her mother does nothing, but after meeting some relatives Grace becomes a bit more understanding, and learns to stand up for herself.